Treatment of localized psoriasis with a topical formulation of zinc pyrithione - Sadeghian, Giti (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2011)
Psoriasis is a common chronic condition of the skin that is resistant to many therapies.To test the efficacy of a topical formulation of zinc pyrithione in an emollient base compared with an emollient alone in the treatment of psoriasis.This was a randomized double-blind clinical trial. Patients with localized psoriasis involving less than 10% of body skin areas were enrolled in the study. They were randomly allocated to one of two treatment groups. Group A was treated with emollient cream containing 0.25% zinc pyrithione and group B was treated with emollient cream alone twice daily for 3 months. Response to treatment was assessed using PASI scores.Of 60 participants, 30 patients in group A and 30 patients in group B completed the study. The mean PASI scores before and after treatment were 3.4 1.8 and 0.9 1.3 in group A (p0.05), and there was a significant difference between the two groups' mean PASI scores at the end of the study (p<0.01). The differences in the mean PASI scores before and after treatment were 2.4 2 and 0.4 0.1 in groups A and B, respectively (p<0.01).A topical formulation of zinc pyrithione can be used to treat localized psoriasis.
Keywords: Administration, Topical; Drug Therapy; Emoliensi; Emollients; Psoriasis; Psoriaza; therapy; Treatment Outcome; Zdravilo, lokalna uporaba; zdravljenje; Zdravljenje, izid